2019
DOI: 10.3389/fclim.2019.00006
|View full text |Cite
|
Sign up to set email alerts
|

Negative Emissions: Priorities for Research and Policy Design

Abstract: The large-scale removal of carbon dioxide from the atmosphere is likely to be important in maintaining temperature rise "well below" 2 • C, and vital in achieving the most stringent 1.5 • C target. Whilst various literature efforts have estimated the global potential of carbon dioxide removal (CDR) for a range of technologies with different degrees of certainty, regional bottlenecks for their deployment remain largely overlooked. Quantifying these barriers, through national and local case studies, rather than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 57 publications
(36 citation statements)
references
References 50 publications
(66 reference statements)
0
36
0
Order By: Relevance
“…A narrow understanding of feasibility generated by, for example, considering the potential of NETs in isolation from one another rather than as a portfolio, or not considering sociocultural or institutional dimensions, risks creating unrealistic expectations regarding the potential of NETs deployment (Fajardy et al, 2019;Low and Schäfer, 2020). This is problematic, because it has been shown that for example social acceptance can be an important barrier to the deployment of new technologies (Lock et al, 2014;Dowd et al, 2015).…”
Section: Feasibility Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A narrow understanding of feasibility generated by, for example, considering the potential of NETs in isolation from one another rather than as a portfolio, or not considering sociocultural or institutional dimensions, risks creating unrealistic expectations regarding the potential of NETs deployment (Fajardy et al, 2019;Low and Schäfer, 2020). This is problematic, because it has been shown that for example social acceptance can be an important barrier to the deployment of new technologies (Lock et al, 2014;Dowd et al, 2015).…”
Section: Feasibility Discussionmentioning
confidence: 99%
“…Emission pathways from Integrated Assessment Models (IAMs) most prominently feature Bioenergy with Carbon Capture and Storage (BECCS) and afforestation/reforestation (IPCC, 2018). While some approaches, such as afforestation/reforestation, have a long history in climate mitigation, the envisioned deployment scale in these pathways exceeds anything that has been deployed before (Fajardy et al, 2019;Carton et al, 2020). As NETs have not yet been scaled up, assessing the feasibility of deploying such technologies at a larger scale inevitably involves uncertainties about their implementation, effectiveness, and side effects (IPCC, 2018).…”
Section: Feasibility Operationalized In Nets Assessmentsmentioning
confidence: 99%
See 2 more Smart Citations
“…Financial viability of such projects will depend on a utilitarian carbon market that caters for negative emissions as well as an appropriate carbon price that incentivizes deployment (Hansson et al 2019). Therefore, policy should look at ways to strengthen carbon pricing mechanisms and introduce negative emissions as a new class of tradeable credits (Fajardy et al 2019).…”
Section: Bioenergy Carbon Capture and Storagementioning
confidence: 99%